Efficient digital beamforming for medical ultrasound imaging - Gao, Changqing (2008)
This work explored several effcient digital beamforming techniques for potential development of a cost effective front-end of a home based ultrasonic imaging system. Efforts have been made to reduce the system computational complexity and/or required hardware resources while achieving an adequate image quality.